A constituição do ethos feminino da personagem Maria Moura, de Rachel de Queiroz - Novais, Caroline Batista Fantini de (2016)
This dissertation is included on the research line "Text and speech in oral and written", the Program of Post graduate Studies in Portuguese Language at the Pontific Catholic University of Sao Paulo. The theme is "The constitution of the feminine ethos of the character Maria Moura, of Rachel de Queiroz" was born a look based on the discursive construction by common sense. In this paper, we analyze a work of brazilian literature representing social values set in a historical moment, the nineteenth century. Is the feminine discourse rhetorical devices that give life to new ways of thinking and understanding reality. The work Memorial of Maria Moura, published in 1992, has a speech likely to analyze the situation of women, based on the rhetoric load protagonist Maria Moura. From this perspective, the analysis is based on the arguments of a character-narrator and female, owner of a fictional ethos created by writer Rachel de Queiroz. The narrative reveals to the reader the dominant institutionalized discourse that dictated the female condition of being in the world. Maria Moura, through rhetoric, makes its effective speech to move the passions that brings truth to the narrative. For being a literary text, the movement of the passions allows to the audience to conduction one or more interpretations regarding the condition of women. The theoretical basis is based on studies of Reboul (1998), Aristotle (2001), Meyer (2007), Perelman and Olbrechts-Tyteca (2005) and Ferreira (2010). For the historical approach, it was traced an overview of the family and the woman, through the searchers Bauer (2001), Del Priore (2000), Quintas (2005) and Rocha-Coutinho (1994). To prove the effectiveness of the speech of the characternarrator Maria Moura, we use rhetorical analysis capabilities. The results obtained in the work allowed the conclusion that women's history, marked by the "cancellation of being" begins to give way to a discursive construction guided by gradual social changes in female behavior